Extracurricular physical exercise and self-education expectations among Chinese teenagers - Xiao, Qin; Tang, Fengyun (Frontiers in Psychology, 2025)
Drawing on data from 16,540 seventh and ninth graders from the China Education Survey (CES), the study employs descriptive statistics and Ordinal Logistic Regression (Ologit) models. These methods dissect the variances in self-education expectations among different youth groups and unravel the effects and heterogeneity of after-school physical exercises on these expectations. The study has two main findings: First, there is a marked difference in self-education expectations between adolescents who engage in extracurricular physical exercise and those who do not. Specifically, the group participating in these activities shows a 20.62% higher expectation than their non-participating peers, male students exhibit a 26.57% increase in self-education expectations, while female students show a 15.21% increase. Then, the impact of extracurricular physical exercise on self-education expectations is significantly influenced by cognitive abilities, academic performance, health status, confidence level, and family factors. The most pronounced effects are observed in self-confidence (b = 0.6490, p < 0.01), cognitive ability (b = 0.2363, p < 0.01), and health status (b = 0.1541, p < 0.01). The findings suggest that interventions to increase physical exercise among adolescents should be sensitive to the diverse needs of different demographic groups and consider the key role of familial background and socio-economic conditions.